Manajemen Tatakelola BUMDES: Mengelola Pemasaran Produk - Andi Yulianto; Mukson Mukson; Otong Saeful Bachri; Slamet Bambang Riono; Yenny Ernitawati (LPPM Universitas Muhadi Setiabudi, 2020)
In its work in Jatimakmur Village, Songom District, Brebes, already has a BUMDes